2015
DOI: 10.1001/jamaophthalmol.2015.57
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy-Related Complications in Olmsted County, Minnesota, 1985 Through 2010

Abstract: IMPORTANCE Trabeculectomy is the surgical standard of care for patients with medically refractory glaucoma. The use of antimetabolite agents, such as mitomycin, has increased the rate of complications after trabeculectomy.OBJECTIVE To determine the rate of trabeculectomy-related complications during a 25-year study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 34 publications
2
44
1
1
Order By: Relevance
“…This predisposes to thin walled, avascular blebs which lead to frank bleb leaks and have a decreased capacity for healing, possibly related to a limited blood supply causing ischemia 6,2629. Neither anti-fibrotic agent was found to confer a greater risk for BRI (Tables 2 and 3), which concurs with other studies 5,8,12,13. The duration of exposure to the anti-fibrotic agent was also not significant ( P =0.73).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This predisposes to thin walled, avascular blebs which lead to frank bleb leaks and have a decreased capacity for healing, possibly related to a limited blood supply causing ischemia 6,2629. Neither anti-fibrotic agent was found to confer a greater risk for BRI (Tables 2 and 3), which concurs with other studies 5,8,12,13. The duration of exposure to the anti-fibrotic agent was also not significant ( P =0.73).…”
Section: Discussionsupporting
confidence: 88%
“…The current premise is that blebitis precedes and leads to BRE if left untreated. While nearly all studies agree that diabetes, inferior bleb position, bleb leak and bleb manipulation are strong risk factors for BRI, dispute exists over others, such as age and gender 6,8,9,1113. It is therefore pertinent that our study examines the risk factors in our population and their impact on the development of BRI.…”
Section: Introductionmentioning
confidence: 96%
“…From previous literature, there were varying rates of short-term complications (from 2 weeks to 1 year after trabeculectomy) ranging from 5.2% to 50%. [456789] Our result is quite similar to the collaborative initial glaucoma treatment study (CIGTS)[5] which found early postoperative complications in 232 eyes (50%) during the first month after initial trabeculectomy even though most of the participants in the CIGTS were Caucasian or of African descent. Unlike our population, all the participants were never exposed to topical medications before trabeculectomy, and a limbus-based conjunctival flap technique without MMC use was used.…”
Section: Discussionsupporting
confidence: 83%
“…The previous studies reported various rates[456789] and types of complications after trabeculectomy. Risk factors which were relevant for the development of complications and surgical failure were also different among studies.…”
mentioning
confidence: 99%
“…Hypotony was defined as a subject maintaining an IOP level of no greater than 5 mm Hg. The remaining list of complications included choroidal effusion, choroidal hemorrhage, hyphema, microhyphema, and aqueous misdirection [10]. …”
Section: Methodsmentioning
confidence: 99%